2019
DOI: 10.1016/j.jns.2019.10.1109
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of satralizumab as monotherapy in pre-specified subgroups of SAkuraStar, a double-blind placebo-controlled phase 3 clinical study in patients with neuromyelitis optica spectrum disorder (NMOSD)

Abstract: Poster Session 2Efficacy of satralizumab as monotherapy in pre-specified subgroups of SAkuraStar, a double-blind placebo-controlled phase 3 clinical study in patients with neuromyelitis optica spectrum disorder (NMOSD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Studies that emphasize the efficacy of anti-interleukin 6 receptor antibodies, e.g., sartralizumab and tocilizumab, underline the importance of interleukin 6 as a B cell-activating factor in NMOSD. [29][30][31] MOGAD MOG, myelin oligodendrocyte glycoprotein, is a minor component of CNS myelin expressed on its outer layer. Conformation-dependent antibodies have been described in a number of CNS inflammatory disease, but recent evidence suggests that MOG IgG-associated disease (MOGAD), affecting children and adults, is a distinct clinical and pathologic entity with optic neuritis, myelitis, isolated brainstem, encephalitis, encephalopathic, or acute disseminated encephalomyelitis-like presentation.…”
Section: Rituximabmentioning
confidence: 99%
“…Studies that emphasize the efficacy of anti-interleukin 6 receptor antibodies, e.g., sartralizumab and tocilizumab, underline the importance of interleukin 6 as a B cell-activating factor in NMOSD. [29][30][31] MOGAD MOG, myelin oligodendrocyte glycoprotein, is a minor component of CNS myelin expressed on its outer layer. Conformation-dependent antibodies have been described in a number of CNS inflammatory disease, but recent evidence suggests that MOG IgG-associated disease (MOGAD), affecting children and adults, is a distinct clinical and pathologic entity with optic neuritis, myelitis, isolated brainstem, encephalitis, encephalopathic, or acute disseminated encephalomyelitis-like presentation.…”
Section: Rituximabmentioning
confidence: 99%
“…The main pathological mechanism involved in the background to NMO is associated with autoreactive anti-AQP4 IgG antibodies. Their relevant role has been confirmed in experimental models (NMO pathology was induced in rats after recombinant IgG transfer) as well as in clinical studies (anti-AQP4 IgG level correlated with relapse activity and the extent of spinal cord lesions shown in MRI) [ 15 , 16 , 17 ].…”
Section: Pathogenesis Of Nmodsmentioning
confidence: 96%
“…In both trials clear differences in the disease outcomes were observed between subjects who were seropositive and seronegative for anti-AQP4 Ig, with a disadvantage for the latter. The safety profile and tolerability of satralizumab were good, without remarkable adverse events [ 16 , 68 ]. In 2020 satralizumab was also approved by the FDA as the therapy for seropositive NMO patients.…”
Section: Current Nmods Treatmentmentioning
confidence: 99%
“…More recently, results have become available for satralizumab monotherapy in NMOSD. In the SAkuraStar study, the efficacy and safety of satralizumab was compared to placebo for relapse prevention in patients with NMOSD [47]. In this phase 3, double-blind, placebo-controlled study, 95 patients were randomised 2:1 to satralizumab (120 mg s.c.) or placebo, administered at weeks 0, 2, 4 and every four weeks thereafter.…”
Section: Satralizumabmentioning
confidence: 99%